Biohydrogen production by deep eutectic solvent delignification-driven enzymatic hydrolysis and photo-fermentation: Effect of liquid–solid ratio. (April 2022) - Jing, Yanyan; Li, Fang; Li, Yameng; Jiang, Danping; Lu, Chaoyang; Zhang, Zhiping; Zhang, Quanguo
Graphical abstract: Highlights: Liquid-solid ratio of 25:1 was optimal for the DES pretreatment process. The highest delignification efficiency with DES pretreatment was 83.12%. DES pretreatment promoted cellulase infiltration and enzymatic hydrolysis. Highest hydrogen yield of pretreated corncob was 3.1 times than that of untreated. Lag time of PFHP was shortened by 50% after pretreatment at a ratio of 25:1. Abstract: Deep eutectic solvent (DES), a new green solvent, was used to pretreat corncob to enhance biohydrogen production. As a result of the pretreatment, lignin was effectively removed, and the maximum delignification efficiency of 83.12% was achieved. Moreover, the contents of cellulose in the pretreated corncob significantly increased. DES pretreatment effect improved with increasing liquid–solid ratio. The pretreated corncob's enzymatic saccharification activity and hydrogen production were promoted due to the lower content of lignin. The best result was observed at a ratio of 25:1 (DES:corncob, g/g), in which the reducing sugar concentration (53.91 g/L) and the hydrogen yield (151 mL/g) was 6.8 and 3.1 times than that of untreated corncob, respectively. In addition, the lag time of hydrogen production was obviously shortened to 16.53 h due to the utilization of abundant available fermentable sugars, which accelerated hydrogen production.